Transcriptomic Analysis of Sex-Associated Degs in Female and Male Flowers of Kiwifruit (Actinidia Deliciosa [a. Chev] C. F. Liang & a. R. Ferguson) - Gonzalez-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Kiwifruit (Actinidia deliciosa [A. Chev.], C.V. Liang & A. R. Ferguson, 1984) is a perennial plant, with morphologically hermaphroditic and functionally dioecious flowers. Fruits of this species are berries of great commercial and nutritional importance. Nevertheless, few studies have analyzed the molecular mechanisms involved in sexual differentiation in this species. To determine these mechanisms, we performed RNA-seq in floral tissue at stage 60 on the BBCH scale in cultivar ‘Hayward’ (H, female) and a seedling from ‘Green Light’ × ‘Tomuri’ (G × T, male). From these analyses, we obtained expression profiles of 24,888 (H) and 27,027 (G × T) genes, of which 6413 showed differential transcript abundance. Genetic ontology (GO) and KEGG analysis revealed activation of pathways associated with the translation of hormonal signals, plant-pathogen interaction, metabolism of hormones, sugars, and nucleotides. The analysis of the protein-protein interaction network showed that the genes ERL1, AG, AGL8, LFY, WUS, AP2, WRKY, and CO, are crucial elements in the regulation of the hormonal response for the formation and development of anatomical reproductive structures and gametophytes. On the other hand, genes encoding four Putative S-adenosyl-L-methionine-dependent methyltransferases (Achn201401, Achn281971, Achn047771 and Achn231981) were identified, which were up-regulated mainly in the male flowers. Moreover, the expression profiles of 15 selected genes through RT-qPCR were consistent with the results of RNA-seq. Finally, this work provides gene expression-based interactions between transcription factors and effector genes from hormonal signaling pathways, development of floral organs, biological and metabolic processes or even epigenetic mechanisms which could be involved in the kiwi sex-determination. Thus, in order to decode the nature of these interactions, it could be helpful to propose new models of flower development and sex determination in the Actinidia genus. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.